Characteristics and behaviors of microplastics undergoing photoaging and Advanced Oxidation Processes (AOPs) initiated aging - Hu, Jinyuan; Lim, Fang Yee; Hu, Jiangyong (Water research (Oxford), 2023)
•The adsorption of aged MPs for PPCPs and heavy metals is a combined effect of physiochemical interactions.•Hydroxyl radical is the main factor leading to the photoaging and AOPs-induced aging of MPs.•Two emerging techniques, 2D-COS-FTIR and EEM-PARAFAC, can be employed for aging process analysis.•Factors affecting the aging of MPs include pH, NOM, halogen ions, biofilm, and plastic additives.•Future research on the mineralization of MPs is an extension of the aging study by AOPs. The fact that 94% of microplastics (MPs) ubiquitous in the environment are subject to natural weathering makes the aging study currently a research hotspot. This review summarized the physicochemical characteristics of MPs undergoing natural and artificial aging and evaluated current analytical methods used in aging studies. Besides, the differences in photoaging and aging induced by advanced oxidation processes (AOPs) were discussed, leading to a conclusion that AOPs composed of oxidant and ultraviolet (UV) irradiation can better facilitate the alteration of MPs compared to UV irradiation alone. In addition, the environmental behavior of aged MPs was outlined and their adsorption properties for organics and metals were highlighted as a result of combined effects of hydrophobic, π–π, diffusion, and hydrogen bond interaction. Furthermore, the mechanisms of photoaging and AOPs-initiated aging were analyzed, mainly the role of reactive oxygen species (ROS) and environmentally persistent free radicals (EPFRs). Finally, the applications of two-dimensional correlation spectroscopy (2D-COS) and three-dimensional fluorescence spectra using excitation emission matrix-parallel factor analysis (EEM-PARAFAC) were discussed for the aging process analysis. This overview plays an important role in explaining the aging characteristics of MPs and provides a theoretical foundation for further investigations into their toxicity and removal. [Display omitted]